Sie sind auf Seite 1von 16

UNIVERSITI TUN HUSSEIN ONN MALAYSIA

FINAL EXAMINATION
SEMESTER I
SESSION 2009/2010

SUBJECT : ENGINEERING MATHEMATICS I

CODE : BSM 1913

COURSE : 1 BFF / 2 BFF / 3 BFF


1 BDP / 2 BDP / 3 BDP / 4 BDP
1 BEE / 2 BEE / 3 BEE / 4 BEE

DATE : NOVEMBER 2009

DURATION : 3 HOURS

INSTRUCTION : ANSWER ALL QUESTIONS IN PART A


AND THREE (3) QUESTIONS IN PART B

THIS EXAMINATION PAPER CONSISTS OF 6 PAGES


BSM 1913

PART A

dy
Q1 (a) If y sin −1 x = sinh −1 y , find by using implicit differentiation.
dx
(5 marks)

(b) Find the arc length of the parametric curve x = cos 3 t and y = sin 3 t over the
3
interval t = π to t = π .
2
(8 marks)

(c) Show that the area of surface that is generated by revolving the arc of x 2 − 4 y = 0
4
about the y-axis from y = 1 to y = 3 is π (16 − 4 2 ) .
3
(7 marks)

Q2 (a) Determine the radius of convergence for the following power series.

(−3) n

n =0 n 7
n +1
( x − 5) n

(7 marks)

(b) Let f ( z ) = e z . Obtain


(i) the Maclaurin series expansion of f (z).
(ii) the Taylor series expansion of f (z) at the point z = 2.
(7 marks)

(c) Given the power series of



(−1) n x n +1
ln(1 + x) = ∑ .
n =0 n +1
Find the
(i) differentiation of the power series of ln(1 + x) .
(ii) integration of the power series of ln(1 + x) .
(6 marks)

2
BSM 1913

PART B

Q3 (a) Evaluate
(i) lim( x 2 + 4 x − x) .
x →∞

(ii) lim 3xe −2 x .


x →∞

x2 − 4
(iii) lim .
x→2 e 2− x − 1
(12 marks)

(b) Determine if the following function is continuous at x = 0 .


⎧ x2 − 9
⎪ , −1 ≤ x < 0
⎪ x − 3

f ( x) = ⎨3, x=0

⎪ sin x + 2, 0 < x ≤ 1
⎪⎩ x
(8 marks)

1 1 dy
Q4 (a) If x = and y = , find when t = 2 .
1− t 2
1+ t 2
dx
(4 marks)

(b) Figure Q4 below shows a window that consist a rectangle topped by a semicircle.
The perimeter of the window is p. The area of the window is to be maximized.

p r
L

Figure Q4

(i) Assuming that the length of the rectangle is L and the radius of the semicircle
is r. What is p in terms of L and r?
(ii) If p = 12 , express the area of the window, A, in terms of r. Hence, find the
radius of the semicircle, r, that maximizes the area, A.
(6 marks)

(c) Sketch the rational function


1
f ( x) =
.
x −4 2

Show all the asymptote(s), intersection point(s), extremum and inflection point(s)
(if any) in your sketch.
(10 marks)

3
BSM 1913

3
Q5 (a) Evaluate ∫ 0
(3 − u ) 2 e − 4u du .

(5 marks)

π
x dx
(b) Use the substitution of t = tan
2
to calculate ∫ 2
0 3 + 5 cos x
.

(8 marks)

(c) Find
2 dx
(i) ∫ 0 5 + x2
.

dx
(ii) ∫x 9 − 16 x 2
.

(7 marks)


3n n!
Q6 (a) Discuss the convergence of the series ∑
n =0 n
n
.

(8 marks)

(b) Consider the power series



1
∑4
n =0
n
( x − 1) 2 n +1 .

Find interval of convergence of the given power series.


(12 marks)

4
BSM 1913

FINAL EXAMINATION
SEMESTER / SESSION : SEM I / 2009/2010 COURSE : 1 BFF / BDP / BEE
SUBJECT : ENGINEERING MATHEMATIC I SUBJECT CODE : BSM 1913

Formulae
Indefinite Integrals Integration of Inverse Functions
x n +1 1
∫ 1 − x 2 dx = sin x + C , | x | < 1
−1
∫ x dx = + C, n ≠ −1
n

n +1
1 −1
∫ x dx = ln | x | +C ∫ 1 − x 2 dx = cos x + C , | x | < 1
−1

∫ cos x dx = sin x + C 1
∫ 1 + x 2 dx = tan x + C
−1

∫ sin x dx = − cos x + C −1
∫ 1 + x 2 dx = cot x + C
−1

∫ sec x dx = tan x + C
2

∫ csc x dx = − cot x + C 1
2
∫ | x | x 2 − 1 dx = sec x + C , | x | > 1
−1

∫ sec x tan x dx = sec x + C −1


∫ | x | x 2 − 1 dx = csc x + C , | x | > 1
−1

∫ csc x cot x dx = − csc x + C


∫ e dx = e + C
x x
1
∫ x 2 + 1 dx = sinh x + C
−1

∫ cosh x dx = sinh x + C 1
∫ x 2 − 1 dx = cosh x + C , | x | > 1
−1

∫ sinh x dx = cosh x + C
∫ sech x dx = tanh x + C −1
2

∫ | x | 1 − x 2 dx = sech | x | +C , 0 < x < 1


−1

∫ csch x dx = − coth x + C
2

−1
∫ | x | 1 + x 2 dx = csch | x | +C , x ≠ 0
−1

∫ sech x tanh x dx = −sech x + C


∫ csch x coth x dx = −csch x + C 1
⎧tanh −1 x + C , | x | < 1

∫ 1 − x 2 dx = ⎨ −1
⎪⎩coth x + C , | x | > 1

TAYLOR AND MACLAURIN SERIES

f ′′(a ) f ′′′(a )
f ( x) = f ( a ) + f ′( a )( x − a ) + ( x − a) 2 + ( x − a) 3 + L
2! 3!
′′
f ( 0) 2 f ( 0) 3′′′
f ( x ) = f (0) + f ′(0) x + x + x +L
2! 3!

TRIGONOMETRIC SUBSTITUTION
Expression Trigonometry Hyperbolic
x2 + k 2 x = k tan θ x = k sinh θ

x2 − k 2 x = k sec θ x = k cosh θ

k 2 − x2 x = k sin θ x = k tanh θ

5
BSM 1913

FINAL EXAMINATION
SEMESTER / SESSION : SEM I / 2009/2010 COURSE : 1 BFF / BDP / BEE
SUBJECT : ENGINEERING MATHEMATIC I SUBJECT CODE : BSM 1913

Formulae
TRIGONOMETRIC SUBSTITUTION
t = tan 2 x
1 t = tan x

2t 1− t2 2t 1− t2
sin x = cos x = sin 2 x = cos 2 x =
1+ t2 1+ t 2 1+ t2 1+ t2
2t 2dt 2t dt
tan x = dx = tan 2 x = dx =
1− t2 1+ t2 1− t2 1+ t2
IDENTITIES OF TRIGONOMETRY AND HYPERBOLIC
Trigonometric Functions Hyperbolic Functions

e x − e−x
cos 2 x + sin 2 x = 1 sinh x =
2
sin 2 x = 2 sin x cos x
e + e −x
x

cos 2 x = cos 2 x − sin 2 x cosh x =


2
= 2 cos 2 x − 1 cosh x − sinh2 x = 1
2

= 1 − 2 sin 2 x sinh 2 x = 2 sinh x cosh x


1 + tan x = sec x
2 2
cosh 2x = cosh2 x + sinh2 x
1 + cot 2 x = csc 2 x = 2 cosh2 x − 1
2 tan x = 1 + 2 sinh2 x
tan 2 x =
1 − tan 2 x
1 − tanh2 x = sech2 x
tan x ± tan y
tan( x ± y ) = coth2 x − 1 = csch2 x
1 m tan x tan y
sin( x ± y ) = sin x cos y ± sin y cos x 2 tanh x
tanh 2x =
1 + tanh2 x
cos( x ± y ) = cos x cos y m sin x sin y
tanh x ± tanh y
2 sin ax cos bx = sin( a + b) x + sin( a − b) x tanh(x ± y) =
1 ± tanh x tanh y
2 sin ax sin bx = cos(a − b) x − cos(a + b) x
sinh(x ± y) = sinh x cosh y ± sinh y cosh x
2 cos ax cos bx = cos(a − b) x + cos(a + b) x
cosh(x ± y) = cosh x cosh y ± sinh x sinh y

CURVATURE, ARC LENGTH AND SURFACE AREA OF REVOLUTION

d2y | x&&y& − y&&x& | x2 2


⎛ dy ⎞
κ= L=∫
dx 2 [x& 2
+ y& ]
2 3/ 2
x
1 + ⎜ ⎟ dx
⎝ dx ⎠
κ=
1
3/ 2
⎡ ⎛ dy ⎞ 2 ⎤ t2 2 2 2
⎢1 + ⎜ ⎟ ⎥ ⎛ dx ⎞ ⎛ dy ⎞ y
⎛ dx ⎞
L=∫
2
⎜ ⎟ + ⎜ ⎟ dt L=∫ 1 + ⎜⎜ ⎟⎟ dy
⎣⎢ ⎝ dx ⎠ ⎦⎥ t
1 ⎝ dt ⎠ ⎝ dt ⎠ y1
⎝ dy ⎠
x 2
2
⎛d ⎞ y2
⎛d ⎞
2
S = 2π ∫ f ( x) 1 + ⎜ [ f ( x)] ⎟ dx S = 2π ∫ g ( y ) 1 + ⎜⎜ [ g ( y )] ⎟⎟ dy
x
1 ⎝ dx ⎠ y1
⎝ dy ⎠

6
BSM 1913

M – method, A – answer, T – true


Q1
1st method
(a)
y sin −1 x = sinh −1 y
dy −1 y 1 ⎡ dy ⎤
sin x + = ⎢ ⎥
dx 1− x2 1 + y 2 ⎣ dx ⎦
dy 1 dy y
sin −1 x − =−
dx 1 + y dx
2
1− x2
y

dy 1− x2 − y 1+ y2
= =
dx
sin −1 x −
1 1 − x 2 ( 1 + y 2 sin −1 x − 1)
1+ y2

2nd method
y sin −1 x = sinh −1 y
sinh( y sin −1 x) = y
⎡ y dy ⎤ dy
cosh( y sin −1 x) ⎢ + sin −1 x ⎥ =
⎣ 1− x dx ⎦ dx
2

dy −1 dy −y
sin x cosh( y sin −1 x) − = cosh( y sin −1 x)
dx dx 1− x2
−y
cosh( y sin −1 x)
dy 1− x2
=
dx sin −1 x cosh( y sin −1 x) − 1

3rd method
y sin −1 x = sinh −1 y
⎛ sinh −1 y ⎞
x = sin⎜⎜ ⎟
⎝ y ⎟⎠
d d ⎡ ⎛ sinh −1 y ⎞⎤
[ x] = ⎢sin ⎜ ⎟⎟⎥
dx dx ⎣ ⎜⎝ y ⎠⎦
y dy
− sinh −1 y
y ⎞ 1+ y
⎛ sinh −1 dx
2
1 = cos⎜⎜ ⎟⎟
⎝ y ⎠ y2

⎛ sinh −1 y ⎞ ⎡ y dy ⎤
y = cos⎜⎜
2
⎟⎟ ⎢ − sinh −1 y⎥
⎝ y ⎠⎢ 1 + y 2 dx ⎥⎦

y ⎛ sinh −1 y ⎞
cos⎜⎜ ⎟⎟ − y 2
dy 1+ y 2
⎝ y ⎠
= −1
dx sinh y

7
BSM 1913

M – method, A – answer, T – true


4th method
y sin −1 x = sinh −1 y
sinh −1 y
sin −1 x =
y
y dy
− sinh −1 y
1 1+ y 2 dx
=
1− x2 y2
y2 y dy
= − sinh −1 y
1− x2 1+ y2 dx
y y2

dy 1+ y2 1− x2
=
dx sinh −1 y
Q1 dx dy
x = cos 3 t ⇒ = −3 cos 2 t sin t ; y = sin 3 t ⇒ = 3 sin 2 t cos t
(b) dt dt
3
π
L= ∫2 (dx / dt ) 2 + (dy / dt ) 2 dt
π
3
π
=∫2 (−3 cos 2 t sin t ) 2 + (3 sin 2 t cos t ) 2 dt
π
3
π
= ∫2 9(sin 2 t cos 4 t + sin 4 t cos 2 t ) dt
π
3
π
= 3∫ 2
sin 2 t cos 2 t (cos 2 t + sin 2 t ) dt
π
3
π
= 3∫ 2 sin t cos t 1dt
π
3 3
3
π π du π du
= 3∫ 2
sin 2t
dt = 3∫ 2 u cos t = 3∫ 2 u sin t
π 2 π cos t π − sin t
3 3 3
π π π
3 ⎡ cos 2t ⎤ 3 2 ⎡ sin t ⎤ 3 2 2 ⎡ cos t ⎤ 32 2
= ⎢ ⎥ = = 3⎢ ⎥ = = 3⎢ ⎥ =
2 ⎣ − 2 ⎦π 2 ⎣ 2 ⎦π 2 ⎣ −2 ⎦π 2
Q1 dx 2
(c) =
dy 4y
⎛ ⎛ 2 ⎞ ⎞⎟
2

4y ⎜ 1+ ⎜ ⎟ ⎟ dy
3
S = 2π ∫
⎜ ⎜ ⎟ ⎟
1
⎝ ⎝ 4 y ⎠ ⎠
3 3
= 2π ∫ 4 y + 4 dy = 4π ∫ y + 1 dy
1 1

Let u = y + 1 ⇒ du = dy
1
4
= 4π ∫ u du 2
2

[ ]
4
⎡ 2u 3 / 2 ⎤ 4
= 4π ⎢ ⎥ = π 16 − 4 2 (shown)
⎣ 3 ⎦2 3

8
BSM 1913

M – method, A – answer, T – true


Q2 ∞
(−3) n
(a) ∑ n 7 n +1 ( x − 5)
n

n =0

(−3) n +1
( x − 5) n +1
a n +1 (n + 1) 7 n + 2
ρ = lim = lim
n →∞ an n →∞ (−3) n
n +1
( x − 5) n
n7
− 3n
= | x − 5 | lim
n →∞ (n + 1) 7
−3 − 3n
= | x − 5 | lim = | x − 5 | lim
n →∞ (1 + 1 / n)7 n →∞ 7n + 7
−3 −3
= | x − 5 | lim = | x − 5 | lim
n →∞ 7 n →∞ 7
3 3
= | x −5| | x−5| =
7 7
3 7
converges if | x − 5 | < 1 ⇒ | x − 5 | <
7 3
3 7
diverges if | x −5| >1⇒ | x −5| >
7 3

7
The radius of the convergence for the series is, ρ = .
3
Q2
We have
(b)
f ( z) = f ' ( z) = f " ( z) = L = f (n) ( z) = e z
we get

f ( n ) ( z ) e z0
f ( z ) = ∑ a n ( z − z 0 ) where a n =
n
=
n =0 n! n!
Q2 1st method
(b) f ( n ) (0) e 0 1
(i) Here, z 0 = 0 and a n = = =
n! n! n!
Therefore
1 2 1 3
ez = 1+ z + z + z +L
2! 3!
2 3
z z
= 1+ z + + +L
2 3
2nd method
f ′′(0) 2
f ( z ) = f (0) + f ′(0) z + z +L
2!
e0 e0
e z = e 0 + (e 0 ) z + z 2 + z 3 + L
2! 3!
2 3
z z
= 1+ z + + +L
2 3

9
BSM 1913

M – method, A – answer, T – true


Q2 1st method
(b)
f ( n ) (2) e 2
(ii) Here, z 0 = 2 and a n = =
n! n!
1 2 1
e z = e 2 + e 2 ( z − 2) + e ( z − 2) 2 + e 2 ( z − 2) 3 + L
2! 3!
1 1
= e 2 + e 2 ( z − 2) + e 2 ( z − 2) 2 + e 2 ( z − 2) 3 + L
2 6

2nd method
f " (a)
f ( z ) = f (a) + f ' (a)( z − a) + ( z − a) 2 + L
2!
1 1
e z = e 2 + e 2 ( z − 2) + e 2 ( z − 2) 2 + e 2 ( z − 2) 3 + L
2! 3!
2
e 1
= e 2 + e 2 ( z − 2) + ( z − 2) 2 + e 2 ( z − 2) 3 + L
2 6
Q2 1st method
(c) d d ⎡ ∞ (−1) n x n +1 ⎤ ∞ d ⎡ (−1) n x n +1 ⎤
[ln(1 + x)] = ⎢∑ ⎥=∑ ⎢ ⎥
dx dx ⎣ n =0 n + 1 ⎦ n =0 dx ⎣ n + 1 ⎦

(−1) n (n + 1) x n +1−1
=∑
n =0 n +1

= ∑ (−1) n x n = 1 − x + x 2 − x 3 + x 4 − x 5 + L
n =0

2nd method
d d ⎡ ∞ (−1) n x n +1 ⎤
[ln(1 + x)] = ⎢∑ ⎥
dx dx ⎣ n =0 n + 1 ⎦
d ⎡ x2 x3 x4 x5 x6 ⎤
= ⎢ x − + − + − + L⎥
dx ⎣ 2 3 4 5 6 ⎦
= 1 − x + x2 − x3 + x4 − x5 + L
1st method

(−1) n x n +1 ∞
(−1) n x n +1
∫ ln(1 + x)dx = ∫ ∑ n =0 n +1
dx = ∑ ∫
n =0 n +1
dx

(−1) n x n + 2 x2 x3 x4 x5
=∑ = − + − +L
n = 0 ( n + 2)( n + 1) 2 6 12 20
2nd method

(−1) n x n +1
∫ ln(1 + x)dx = ∫ ∑ n =0 n +1
dx

⎡ x2 x3 x4 ⎤
= ∫ ⎢x − + − + L⎥ dx
⎣ 2 3 4 ⎦
2 3 4 5
x x x x
= − + − +L
2 6 12 20

10
BSM 1913

M – method, A – answer, T – true


Q3 1st method
(a)
(i) lim( x 2 + 4 x − x) = lim ( x + 4 x − x) ( x + 4 x + x)
2 2

x →∞ x →∞ 1 ( x 2 + 4 x + x)
x 2 + 4x − x 2
= lim
x →∞
x 2 + 4x + x
4x
= lim x
x →∞
x + 4x x
2
+
x2 x
4
= lim =2
x →∞
1+ 4 / x +1

2nd method (L’Hopital’s rule)


lim ( x 2 + 4 x − x) = lim
x →∞ x →∞
[ 1 + 4 / x − 1]x
1+ 4 / x −1
= lim
x →∞ 1/ x
1
(1 + 4 / x) −1 / 2 (−4 x − 2 )
= lim 2
x →∞ − x −2
4/2
= lim =2
x →∞
1+ 4/ x

Q3 3x
(a) lim 3 xe − 2 x = lim
x →∞ x →∞ e 2 x
(ii) 3
= lim 2 x
x → ∞ 2e

=0
Q3
x2 − 4 2x
(a) lim 2− x
= lim 2− x
(iii)
x→2 e − 1 x→2 − e
= −4
Q3
(b) i) f (0) = 3

x2 − 9 ( x − 3)( x + 3)
ii ) lim = 3 or lim =3
x →0 − x−3 x →0 − x−3
sin x sin x
lim + 2 = lim + lim 2 = 3
x →0 + x x →0 + x x →0+

lim f ( x) = lim f ( x)
x →0− x →0 +

∴ lim f ( x) = 3
x →0

Since lim f ( x) = f (0) = 3 , the function is continuous at x = 0 .


x →0

11
BSM 1913

M – method, A – answer, T – true


Q4 1 1
(a) x= ; y=
1− t 2
1+ t2
dx 2t dy − 2t
= ; =
dt (1 − t )2 2
dt (1 + t 2 ) 2

2
dy dy dt 2t (1 − t 2 ) 2 (1 − t 2 ) 2 ⎛ 1− t2 ⎞
= =− =− = −⎜ 2 ⎟
dx dt dx (1 + t 2 )2 2t (1 + t 2 ) 2 ⎝ 1+ t ⎠
dy 9
=−
dx t = 2 25
Q4 p = π r + 2r + 2 L
(b)
Q4 A = 12 π r 2 + 2 Lr
(b)
= 12 π r 2 + r ( p − π r − 2r )
(ii)
p = 12
A = 12 π r 2 + 12r − π r 2 − 2r 2
= 12r − 12 π r 2 − 2r 2 = 12r − ( 12 π + 2)r 2

dA
= 12 − 2( 12 π + 2)r
dr

When A is maximum,
dA
=0
dr
12 − 2( 12 π + 2)r = 0
12
r=
π +4
d2A 12
= −2( 12 π + 2) < 0 , hence A is maximum when r = .
dr 2
π +4
Q4 1
f ( x) = 2
(c) x −4

when x = 0, f ( x) = − 14
y − intersection: (0, − 14 )

lim f ( x) = ∞ ; lim f ( x) = −∞
x → −2 − x → −2 + x2 − 4 = 0
or
lim f ( x) = −∞ ; lim f ( x) = ∞ x = ±2
x →2− x →2+
∴ x = ±2 is the vertical asymptote.

lim f ( x ) = 0
x →±∞

∴ x = 0 is the horizontal asymptote.

12
BSM 1913

M – method, A – answer, T – true

2x
f ′( x) = −
( x − 4) 2
2

f ' ( x) = 0
x=0

(0, − 14 ) is the critical point.

( x 2 − 4) 2 [2] − 2 x[2( x 2 − 4)2 x]


f " ( x) = −
( x 2 − 4) 4
2( x 2 − 4)[ x 2 − 4 − 4 x 2 ]
=−
( x 2 − 4) 4
2(3x 2 + 4)
=
( x 2 − 4) 3

f ′′( x ) ≠ 0, hence there is no inflection point.

2(4) 1
f ′′(0) = =− <0
(−4) 3
8
∴ (0, − 4 ) is the maximum point.
1

Interval ( −∞ , − 2) –2 (−2, 0) (0, 2) 2 ( 2,+∞ )


x –3 – 0.5 0.5 3
f ′(x ) + + – –
Graph IC VA IC DC VA DC
f ′′(x ) + – – +
Graph CU CD CD CU
f (x)

0
x
-2 2
(0, -1/4)

x = -2 x=2

13
BSM 1913

M – method, A – answer, T – true


Q5 3
(a) ∫ (3 − u ) 2 e − 4u du
0

sign diff int


+ (3 − u ) 2
e −4u
1 − 4u
− − 2(3 − u ) = −6 + 2u e
−4
1 − 4u
+ 2 e
16
1
− 0 − e − 4u
64

3
⎡ e − 4u e − 4u e − 4u ⎤
= ⎢(3 − u ) 2 − (−6 + 2u ) + (2) ⎥
⎣ −4 16 − 64 ⎦ 0
⎧⎡ e −12 ⎤ ⎡ 9 6 2 ⎤⎫
= ⎨ ⎢0 − 0 − ⎥−⎢ + − ⎥⎬
⎩⎣ 32 ⎦ ⎣ − 4 16 64 ⎦ ⎭
61 e −12
= − ≈ 1.9062
32 32
Q5 π /2
dx
(b) ∫0 3 + 5 cos x
2dt
=∫ 1+ t2
⎛1− t 2 ⎞
3 + 5 ⎜⎜ ⎟⎟
⎝1+ t
2

2
=∫ dt
3(1 + t ) + 5(1 − t 2 )
2

2
=∫ dt
8 − 2t 2
1
=∫ dt
4 −t2
1
=∫ dt
(2 − t )(2 + t )
1
use partial fraction : A = B =
4 1 1
1 ⎡ 1 1 ⎤
= ∫
4 1 − ( 2t ) 2
dt
= ∫ ⎢ +
4 ⎣ 2 − t 2 + t ⎥⎦
dt
u= t
; 2du = dt
2

= [− ln | 2 − t | + ln | 2 + t | ]
1 1 1
4 = ∫
4 1− u2
2du
π /2
1⎡ x x ⎤ 1⎡ ⎛ tan 2x ⎞⎤
π /2
= ⎢− ln 2 − tan + ln 2 + tan ⎥ = ⎢ tanh −1 ⎜⎜ ⎟⎟⎥
4⎣ 2 2 ⎦0 2⎣ ⎝ 2 ⎠⎦ 0
1
= ln 3 ≈ 0.275 = 0.275
4

14
BSM 1913

M – method, A – answer, T – true


dx 2 dx
∫ ∫
2
Q5 =
(c) 0 5+ x 2
0 ⎛ x2 ⎞
(i)
5 ⎜⎜1 + ⎟⎟
⎝ 5 ⎠
1 2 dx
= ∫ 2
5 0 ⎛ x ⎞
1 + ⎜⎜ ⎟⎟
⎝ 5⎠

x
Let u =
5
du 1
= ⇒ dx = 5du
dx 5

1 2 1
= ∫
5 0 1+ u2
5 du
2
5 ⎡ −1 x ⎤
=
5 ⎢⎣ ⎥
tan
5⎦0
5
= [0.7297 − 0] = 0.3263
5

dx dx
∫x =∫
Q5
(c) 9 − 16 x 2 ⎛ 16 x 2 ⎞
x 9⎜⎜1 − ⎟
9 ⎟⎠
(ii)

dx
=∫
16 x 2
x 9 1−
9
dx
=∫
2
⎛4 ⎞
3x 1 − ⎜ x ⎟
⎝3 ⎠

4 3
Let u = x ⇔ x= u
3 4
du 4 3
= ⇒ dx = du
dx 3 4

1 1 3
= ∫
3 ⎛3 ⎞ 2 4
du
⎜ u⎟ 1− u
⎝4 ⎠
1 4
= − sech −1 x + C
3 3

15
BSM 1913

M – method, A – answer, T – true


Q6 ∞
3n n!
(a) ∑ n n
n =0

a n +1 3 n +1 (n + 1) ! n n
ρ = lim = lim .
n →∞ a
n
n→∞ (n + 1) n +1 3 n n!
3 n 3 (n + 1)n! n n 3n n
= lim ⋅ = lim
n →∞ (n + 1) n (n + 1) 3 n n! n →∞ ( n + 1) n

n
⎛ n ⎞
= 3 lim ⎜ ⎟
n →∞
⎝ n + 1⎠
3
use L Hopital ' s rule =
e
3
Qρ = > 1 , so the given series is divergent
e
Q6 ∞
1
(b) ∑4
n =0
n
( x − 1) 2 n +1

a n +1 ( x − 1) 2 ( n +1) +1 4n
ρ = lim = lim ⋅
n →∞ an n→∞ 4 n +1 ( x − 1) 2 n +1
( x − 1) 2 n +1 ( x − 1) 2 4n
= lim ⋅
n →∞ 4n4 ( x − 1) 2 n +1
1 1
= lim ( x − 1) 2 = ( x − 1) 2
n →∞ 4 4
.
1
So the series converges for ( x − 1) 2 < 1 ⇔ | x − 1 | < 4
4

So the radius of convergence is R = 2 and


− 2 < x − 1 < 2 ⇔ −1 < x < 3

Checking the endpoints:



1
For x = −1 : ∑ n ( −1 − 1) 2 n +1
n =0 4

1 23 25
= ∑ n (−2) 2 n +1
= −2 − − − L = −2 − 2 − 2 − L
n =0 4 4 4
The series diverges.


1
For x = 3 : ∑4
n =0
n
(3 − 1) 2 n +1

1 23 25
=∑ n
( 2) 2 n +1
= 2 + + + L = 2 + 2 + 2 + L.
n =0 4 4 4
The series diverges.

So the interval of convergence is − 1 < x < 3 .

16